ESPOSITO DAN KAPITALISME DI BUMI ISLAM Kajian Hak Milik Pribadi, Privatisasi dan Intervensi Negara, serta Kesenjangan Buruh-Majikan - Maghfur Ahmad (IAIN Pekalongan, 2014)
This research study Esposito views about Islam's rejection of capitalism. Background of this study is his book What Everyone Needs to Know About Islam, section